Purification of a factor that promotes neurite outgrowth: isolation of laminin and associated molecules (The Rockefeller University Press, 1985)
When culture medium, conditioned by any of several cell types, is applied to a polycationic substratum, a substance is adsorbed that causes neurons cultured on that substratum to extend processes (neurites) rapidly and profusely. We have purified the factor responsible for this effect from medium conditioned by bovine corneal endothelial cells, and have shown that it is composed of the glycoprotein laminin and two associated laminin-binding molecules: a sulfated protein known as entactin, and a large heparan sulfate proteoglycan. Of these molecules, only laminin was found to be present throughout the purification in all fractions possessing neurite outgrowth-promoting activity and absent from all fractions lacking activity. Laminin, purified from other sources, has been shown previously to promote extensive outgrowth by cultured neurons. These and other data presented here support the conclusion that laminin is responsible for the neurite outgrowth-promoting activity of the conditioned medium factor. Evidence is also presented that the association of a proteoglycan with laminin promotes efficient attachment of laminin to polycationic substrata, particularly in the presence of competing molecules.